THE EFFECT OF PROFITABILITY, LEVERAGE AND ACTIVITY ON STOCK RETURNS IN BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Safena Kurnia Syahputri; Sunarto Sunarto (Jurnal Ekonomi, 2023)
This study aims to examine the effect of profitability, leverage, and activity on stock returns through annual financial reports that have been prepared by banking companies listed on the Indonesia Stock Exchange. While the dependent variable is stock returns. The sample in this study was obtained using a purposive sampling method for banking companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2021 period, and 42 banking companies with 200 observations. The analytical method used is multiple regression analysis with the SPSS (Staticical Product and Service Solutions) application tool. The results showed that profitability has a positive effect on stock returns, while leverage and activity have no effect on stock returns.